Analysis on the Incidence of the Fibularis Quartus Muscle Using Magnetic Resonance Imaging. (9th July 2012) - Rios Nascimento, Sérgio Ricardo; Watanabe Costa, Renata; Ruiz, Cristiane Regina; Wafae, Nader
Abstract : Objective . Quantify the presence of the fibularis quartus muscle and correlate it with the individual's sex and concomitant presence of the fibularis tertius muscle. Materials and Methods . We evaluated 211 magnetic resonance examinations (43.13% men and 56.87% women) on the ankle and hindfoot, produced between 2009 and 2011. Results . The fourth fibularis muscle was found to be present in 7.62% of the examinations and 75% of these also contained the fibularis tertius muscle. Conclusion . The incidence of the fourth fibularis muscle is variable; moreover, its incidence does not depend on the individual's gender or the presence of the fibularis tertius muscle.